TINGKAT PENGETAHUAN MASYARAKAT PERUMAHAN PONDOK GEDE JEMBER TERHADAP PENGGUNAAN ANTIBIOTIK TANPA RESEP DOKTER (Periode Juni 2022) - Asa Falahi; Novia Ananta Budiono; Amaliyah Nurul Hidayah; Rosida Rosida (AKADEMI FARMASI JEMBER, 2022)
Antibiotics are drugs used to treat bacterial infections and including in a group of strong drugs that are only purchased at pharmacies with doctor's prescription. Inappropriate use of antibiotics can lead to less effective treatment, an increased risk of patient death, widespread resistance, and high treatment costs. The purpose of this study was to know the society knowledge level in Perumahan Pondok Gede RT 06 RW 33 Kaliwates Jember about using antibiotics without a doctor's prescription. The type of this study was a descriptive survey research with a cross-sectional method. Sampling technique used purposive sampling with an inclusion criteria and obtain 60 samples. Based on research and data analysis obtain the percentage level of knowledge in 3 domains, in the know realm was 61% (enough category), in the understanding realm was 52% (less category), and 58% in the application realm (enough category). It can be concluded that the society knowledge level in Perumahan Pondok Gede RT 06 RW 33 is enough category about using antibiotics without doctor’s prescription.